Effects of Heat Treatment on the Microstructure and Mechanical Properties of Selective Laser Melting 316L Stainless Steel - Jingfa Lei; Yongsheng Ge; Tao Liu; Zhan Wei (Shock and Vibration)
316L stainless steel materials are widely used in impact-resistant structures. Heat treatments could affect the mechanical properties of 316L stainless steel parts formed by selective laser melting (SLM), which is vital for ensuring service safety. This study aimed to analyze the mechanical behavior of SLM 316L stainless steel under different heat treatment methods. Therefore, test specimens were prepared using the SLM technique and then annealed at 400°C for 1 h. The solution was treated at 1050°C for 20 min. The dynamic compressive mechanical properties of the deposited, annealed, and solution-treated specimens were tested at high strain rates by using a split Hopkinson pressure bar (SHPB) experimental apparatus. Moreover, the microstructures of the previously mentioned samples were analyzed by optical microscopy and scanning electron microscopy. The experimental results showed that the three-state samples exhibited strain rate sensitivity in the dynamic mechanical tests and that solution treatment could alter their mechanical properties significantly. In addition, the microstructure of the deposited specimens presented cylindrical cellular crystal features, which have a higher dislocation density. Hence, the yield strength of deposited specimens is higher than that of the solution-treated ones. After annealing, the microstructures of the samples did not change obviously, and their dynamic yield strength remained almost unchanged. After solution treatment, its cellular crystal disappeared and dislocation density dropped dramatically, resulting in a sharp decrease in yield strength. Finally, this research can provide a theoretical reference for broadening the practical application of SLM 316L material parts.